Active magnetoplasmonic split-ring/ring nanoantennas. Issue 1 (1st December 2016) - Feng, Hua Yu; Luo, Feng; Arenal, Raul; Henrard, Luc; García, Fernando; Armelles, Gaspar; Cebollada, Alfonso
Abstract : We show that the MO effect in the nanoring can be further and greatly enhanced by an additional split-ring nanoantenna atop. Abstract : Here we present a novel active system, which combines the plasmon resonance enhancement of the magneto-optical activity in magnetoplasmonic nanostructures and the strong electromagnetic field localization of split ring resonators. The structures consist of a gold split ring resonator placed on top of a gold nanoring in the section of which a Co nanodot is inserted. By placing the split ring gap on top of the nanodot, and continuously varying the split ring gap opening, we are able to tune and enhance the electromagnetic field intensity in the Co nanodot, as confirmed experimentally by EELS and numerically using DDA simulation methods. In this way we obtain structures with a magneto-optical activity, which is 3 times larger than that of equivalent magnetoplasmonic rings without a split ring on top. These enhanced performances are due to the better control of the positioning, dimensions, and shape of the different components of the system. Such improvements are achieved using hole-mask colloidal lithography technique combined with multiaxial evaporation of the different materials.